Conjugate natural convection heat transfer in an open-ended square cavity partially filled with porous media - Chen, Sheng; Gong, Wei; Yan, Yuying (Elsevier, 2018)
Conjugate natural convection heat transfer in an open-ended square cavity, which is partially filled with porous media, is a useful research prototype to deepen our insight into many important practical applications, such as solar energy collectors. But surprising, until now there is no open literature on it. In addition, for traditional numerical approaches, it is a great challenge to model conjugate problems on fluid-porous interfaces. In the present work, firstly we develop a new lattice Boltzmann (LB) approach to overcome such difficulty. The present LB model is validated by three benchmark tests. With the aid of this LB approach, we investigate the effects of thickness of porous layer, fluid-to-porous thermal conductivity ratio and permeability of porous layer on conjugate natural convection heat transfer in an open-ended porous-partially-filled square cavity, for the first time. It is found that these factors all influence the patterns of flow field and temperature field significantly. Especially, there exist some critical values. A small offset from them will cause a substantial change of heat and mass transfer. Sometimes the change trends are completely reversed. The present results may provide useful theoretical guides for the relevant practical applications.